Study on IGBT Reliability of Rail Transit Traction Converter Application - XIN Li; RONG Zhilin; DOU Zechun; XIN Lanyuan; FU Hangjie (机车电传动)
For the purpose of improving the system reliability of electric locomotive traction, based on the study of IGBT failure mechanism and failure models, IGBT failure rates of different types of locomotives in each operating region were compared. The failure causes were analyzed, and the specific solutions were provided as well. It provided certain basis for the deep study of rail transit traction converter application reliability.